Modulation of gut microbiota from obese individuals by in vitro fermentation of citrus pectin in combination with Bifidobacterium longum BB-46 - Bianchi, Fernanda [UNESP]; Larsen, Nadja; de Mello Tieghi, Thatiana [UNESP]; Adorno, Maria Angela Tallarico; Kot, Witold; Saad, Susana Marta Isay; Jespersen, Lene; Sivieri, Katia [UNESP] (Springer Nature, 2018)
This study aimed to evaluate the effects of three treatments, i.e., Bifidobacterium longum BB-46 (T1), B. longum BB-46 combined with the pectin (T2), and harsh extracted pectin from lemon (T3) on obesity-related microbiota using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®). The effects of the treatments were assessed by the analysis of the intestinal microbial composition (using 16S rRNA gene amplicon sequencing) and the levels of short-chain fatty acids (SCFAs) and ammonium ions (NH4 +). Treatments T2 and T3 stimulated members of the Ruminococcaceae and Succinivibrionaceae families, which were positively correlated with an increase in butyric and acetic acids. Proteolytic bacteria were reduced by the two treatments, concurrently with a decrease in NH4 +. Treatment T1 stimulated the production of butyric acid in the simulated transverse and descending colon, reduction of NH4 + as well as the growth of genera Lactobacillus, Megamonas, and members of Lachnospiracea. The results indicate that both B. longum BB-46 and pectin can modulate the obesity-related microbiota; however, when the pectin is combined with B. longum BB-46, the predominant effect of the pectin can be observed. This study showed that the citric pectin is able to stimulate butyrate-producing bacteria as well as genera related with anti-inflammatory effects. However, prospective clinical studies are necessary to evaluate the anti/pro-obesogenic and inflammatory effects of this pectin for future prevention of obesity.
Keywords: 16S rRNA sequencing; Bifidobacterium longum BB-46; Obese microbiota; Pectin; SHIME® model